Developmental defects associated with glucosamine auxotrophy in Saccharomyces cerevisiae - Ballou, Clinton E. (1977)
Saccharomyces cerevisiae mutants, unable to make D-glucosamine owing to a defect in the enzyme 2-amino-2-deoxy-D-glucose-6-phosphate ketol-isomerase (amino-transferring) (EC 5.3.1.19), show aberrations both in sporulation and in vegetative growth. They grow normally on a medium of yeast extract, peptone, and dextrose (YEPD) containing D-glucosamine (1 mg/ml), and such cells accumulate 4 to 5 times the amount of D-glucosamine present in wild-type cells cultured on YEPD alone. When such mutant cells are shifted to YEPD alone, they continue to increase in cell mass for about 10 hr (three to four cell cycles) and produce strings of beads in which the cells fail to separate. Although each of the “cells” contains a nucleus, electron micrographs of thin sections reveal that septation is defective apparently owing to the inability to synthesize chitin, which forms the primary septum in S. cerevisiae. The viability of such cultures drops rapidly after 3-5 hr, a fact attributable to lysis of the cells through wall defects in the septum region where gross disorganization is apparent. When the mutant cells grown on YEPD plus D-glucosamine are transferred to sporulation medium (1% potassium acetate), they proceed through meiosis to produce viable spores that appear to be altered only in the nature of the spore wall. The spores lack a dark-staining surface layer that is visible in thin sections prepared from wild-type cells, they are notably less hydrophobic than wild-type spores, and they are digested and lysed by glucanases that do not affect normal spores. All of these properties suggest that D-glucosamine is required for spore maturation and is used to synthesize a glucanase-resistant hydrophobic surface layer on the primary glucan spore wall. In agreement with this postulate, D-glucosamine synthesis and the activity of the isomerase do not appear until late in meiosis when tetranucleate cells are abundantly present in the sporulation culture.